Implementation of Outbreak: A Population-Based Interprofessional Exercise - Sara Paton; Sheri Gladish; Zachary Jenkins; Sabrina Neeley (Ohio Journal of Public Health, 2024)
In 2016, the Interprofessional Education Collaborative (IPEC) competencies expanded to include the health care needs of populations in addition to patients, and the Council on Education for Public Health (CEPH) added a required interprofessional education (IPE) competency for accredited public health programs. Addressing population health issues requires collaboration between public health and other health professionals, but most IPE education materials focus on patient care rather than population health. This manuscript describes a population-based virtual IPE experience for public health and health professions students. In 2021, a total of 95 medical, pharmacy, public health, and clinical mental health counseling students participated in a virtual, infectious disease outbreak experience. Question prompts highlighted a joint response team’s role in maximizing outcomes while ensuring equity, emphasizing the 2016 IPEC competencies. Jefferson Teamwork Observation Guide (JTOG) results indicated that most participants believed their teams achieved the 14 IPEC competency-based items for interprofessional teamwork. Despite the challenges of hosting this activity in a virtual environment, students found it valuable to their learning. Population health crises introduce unique challenges and uncertainties for health care providers. Establishing interprofessional relationships before a crisis prepares professionals to work with other disciplines. Future emphasis should be placed on facilitator onboarding, technology support, and the students’ understanding of their roles and expectations.
Keywords: Population health; Interprofessional; Emergency preparedness; Outbreak; Virtual